Arabidopsis thaliana Stress Associated Protein 2 (AtSAP2) Expression in Response to Salinity and Drought is Regulated by the RAP2.4 Transcription Factor - Sakri, Iman Afiq; Md Isa, Nurulhikma (Malaysian Applied Biology, 2025)
Plants cannot move to shelter themselves and need to adapt to environmental changes through complex regulatory mechanisms. These adaptations commonly involve the role of stress-related transcription factors (TF). This study explores the role of Ethylene Response Factor (ERF) transcription factor binding sites by examining their distribution within the promoter region of the Arabidopsis thaliana Stress Associated Protein 2 (AtSAP2). Previous studies have highlighted the importance of AtSAP2 in conferring tolerance to plants under abiotic stress, and its ortholog in rice (OsSAP4) has been shown to exhibit increased expression due to ERF binding sites. Thus, understanding the connection between specific ERF sites and the regulation of AtSAP2 is crucial. Analysis of the 2 kb region upstream of the AtSAP2 promoter revealed several Transcription Factor Binding Sites (TFBS), including bZIP, C2H2, CPP, ERF, HD-ZIP, G2-like, MYB, and WRKY. Among these, the Ethylene Response Factor (ERF) binding sites, along with C2H2, are the most abundant in the AtSAP2 promoter. Notably, RAP2.4, an ERF, is significantly predicted to be present in the AtSAP2 promoter (p<0.05). To investigate the relationship between AtSAP2 and RAP2.4 regulation, a promoter study was conducted using Arabidopsis. Two different constructs were generated and transformed into Arabidopsis: Col-0 (pAtSAP2::Col-0) and the rap2.4 mutant (pAtSAP2::rap2.4). The rap2.4 mutant was used to determine whether a mutation in RAP2.4, an ERF, affects AtSAP2 expression through the RAP2.4 binding site. A clear difference in GUS staining activity was observed between pAtSAP2::Col-0 and pAtSAP2::rap2.4. The pAtSAP2::Col-0 plants exhibited blue stain, indicating GUS activity, while no GUS activity was detected in pAtSAP2::rap2.4 plants at either the vegetative (leaf) or inflorescence stage. This suggests that the RAP2.4 protein plays a crucial role in regulating AtSAP2 gene expression through its binding site during abiotic stress.